2015
DOI: 10.1016/j.jep.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Khat use and appetite: An overview and comparison of amphetamine, khat and cathinone

Abstract: Ethnopharmacological relevance To understand the role of khat (Catha edulis) use on the aberrations in appetite and weight which are common comorbidities for khat and other amphetamine users. Materials and methods We provide a comprehensive overview and conceptual summary of the historical cultural use of khat as a natural stimulant and describe the similarities and differences between cathinone (the main psychoactive constituent of khat) and amphetamine highlighting the limited literature on the neurophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 104 publications
(136 reference statements)
1
22
0
Order By: Relevance
“…These differential effects that can be produced by psychostimulants on dopamine and serotonin from in vivo and in vitro findings are interesting [73] due to the following 2 reasons: the inconsistency between in vivo and in vitro findings and the differences in short-and long-term effects of psychostimulants on different regions of the brain (NAc vs. hypothalamus) [74] . Some studies have shown that cathinone has no effect on brain serotonin [68] , while other recent studies have suggested that there is a slight effect [75,76] .…”
Section: Khat and Monoaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…These differential effects that can be produced by psychostimulants on dopamine and serotonin from in vivo and in vitro findings are interesting [73] due to the following 2 reasons: the inconsistency between in vivo and in vitro findings and the differences in short-and long-term effects of psychostimulants on different regions of the brain (NAc vs. hypothalamus) [74] . Some studies have shown that cathinone has no effect on brain serotonin [68] , while other recent studies have suggested that there is a slight effect [75,76] .…”
Section: Khat and Monoaminesmentioning
confidence: 99%
“…However, the aforementioned studies postulate that the effect of khat extract -cathinone -or cathine could produce a change in body weight if given at high doses for a sufficient period to observe the effect. Food Intake Although khat use and its effect on appetite has been reviewed recently [75] , it is worth re-emphasising the dosage and duration of khat. Acute studies (hours) showed consistent findings concerning the suppressant effect of cathinone and cathine ( table 1 ).…”
Section: Khat and Obesitymentioning
confidence: 99%
“…Khat is reported to induce toxic hepatitis together with high-titer anti-nuclear antibody mimicking serologic patterns of autoimmune hepatitis and potentially associated with malignant and malignant oral disorders [15]. ere are several pieces of evidence connecting khat chewing to genetic damage of the oral mucosa and cancer [16,17] Esophageal and gastric carcinoma have been observed in khat chewers in both men and women in Yemen [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this use pattern inhibits work productivity and leads to financial problems . Items grouped in weight control were consistent with appetite suppressant effects of cathinone, one of the main ingredients of khat . Finally, family issues included items that describe unfavourable views toward khat use among women.…”
Section: Discussionmentioning
confidence: 98%